The Cylapinae of French Guiana: an illustrated catalogue with the description of a new species (Insecta, Heteroptera, Miridae) - Chérot, Frédéric; Wolski, Andrzej; Carpintero, Diego Leonardo (Zootaxa, 2023)
An illustrated catalogue of Cylapinae (Insecta, Heteroptera, Miridae) from French Guiana is provided. Valdasus cerdai, n. sp. is described as new. Cylapus antennatus (Carvalho & Fontes, 1968), C. citus Bergroth, 1922, C. ruficeps Bergroth, 1922, C. tucuriensis (Carvalho, 1989) and Peltidocylapus caudatus Wolski, 2021 are recorded from French Guiana for the first time. The validity of Valdasoides Carvalho, 1989 is discussed.